Best Jewish books for children and teens - Silver, Linda R. (The Jewish Publication Society, 2010)
Linda Silver selected the titles that "represent the best in writing, illustration, reader appeal, and authentically Jewish content--in picture books, fiction and non-fiction, for readers ranging from early childhood through the high school years."--Page 4 of cover.